Stateless Zionism: Old traditions, new ideologies - Maor, Zohar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This essay aims at exploring Zionist currents that resisted the establishment of a Jewish nation-state, their non-statist vision of Zionism and its roots in Jewish conditions and political traditions, as well as in European anti-statist ideologies and national patterns. First, the non-Zionist diaspora nationalism of Simon Dubnow will be examined, as an important point of reference of non-statist Zionisms; then, the reservations of Ahad Ha?am, founder of "spiritual Zionism", from the vision of a nation-state and the Marxian anti-statism of Ber Borochov and his socialist followers will be observed.
Keywords: Ginsberg, Aszer Cwi (Ahad Ha'am; pisarz rosyjski; 1856-1927); Borochov, Bor (1881-1917); Dubnow, Simon (żydowski historyk, pisarz; 1860-1941); Buber, Martin (austriacki filozof; 1878-1965); Brit Shalom; nationalism; Zionism